The ecological outcomes of biodiversity offsets under “no net loss” policies: A global review - zu Ermgassen, Sophus O. S. E.; Baker, Julia; Griffiths, Richard A.; Strange, Niels; Struebig, Matthew J.; Bull, Joseph W. (Conservation letters, 2019)
No net loss (NNL) biodiversity policies mandating the application of a mitigation hierarchy (avoid, minimize, remediate, offset) to the ecological impacts of built infrastructure are proliferating globally. However, little is known about their effectiveness at achieving NNL outcomes. We reviewed the English‐language peer‐reviewed literature (capturing 15,715 articles), and identified 32 reports that observed ecological outcomes from NNL policies, including >300,000 ha of biodiversity offsets. Approximately one‐third of NNL policies and individual biodiversity offsets reported achieving NNL, primarily in wetlands, although most studies used widely criticized area‐based outcome measures. The most commonly cited reason for success was applying high offset multipliers (large offset area relative to the impacted area). We identified large gaps between the global implementation of offsets and the evidence for their effectiveness: despite two‐thirds of the world's biodiversity offsets being applied in forested ecosystems, we found none of four studies demonstrated successful NNL outcomes for forested habitats or species. We also found no evidence for NNL achievement using avoided loss offsets (impacts offset by protecting existing habitat elsewhere). Additionally, we summarized regional variability in compliance rates with NNL policies. As global infrastructural expansion accelerates, we must urgently improve the evidence‐base around efforts to mitigate development impacts on biodiversity.